Lacan's Sade: The Politics of Happiness. Issue 3 (November 2015) - Wright, Colin
<x content-type="archive" xml:space="preserve">Abstract</x> This article assesses the contemporary relevance of Sade's work and thought by returning to Jacques Lacan's interpretation of it. It is argued that if the Sadean emphasis on sexual freedom has been co-opted by neoliberal capitalism, this is in part thanks to avant-garde intellectuals of the twentieth century who approached Sade through a simplistically libidinal reading of Freud. By contrast, the article argues that Lacan's more sophisticated reading of Freud enables him in turn to situate Sade amidst eighteenth-century philosophical and political debates regarding, not sexual pleasure or revolutionary desire, but happiness. Lacan shows that Sade was already challenging the modern, and today market-based, notion of a 'right to happiness' with the 'maxim for jouissance' he asserted in La Philosophie dans le boudoir. This more troubling Sade, it is claimed, opens up the possibility of a perverse ethic distinct from the 'polymorphous perversity' characteristic of contemporary consumer culture and its related conceptions of happiness.